TIPOLOGI PESERTA DIDIK PERSPEKTIF FILOSOFIS-PSIKOFISIK PENDIDIKAN ISLAM - Muh. Hamzah; Ach. Waqif Arofah (PEDAGOGIK : JURNAL PENDIDIKAN, 2019)
This study aims to describe the types of students according to the philosophy of Islamic education. Students who are none other than not the main object of the purpose of the process of education, we should know that they have types that are different from one another. The results of this study are that students according to the philosophy of Islamic education study have types, among others; 1) Nativism which says that human humans from birth carry certain innate traits, 2) Empiricism which says that humans are born like blank white paper, 3) Convergence which says that humanity from birth has been provided with two potentials, namely good potential and bad potential.